359 Transportation of cull dairy cows in British Columbia: duration and effects on cow condition. (7th December 2018) - Stojkov, J; Fraser, D
Abstract: Cull dairy cows are regularly removed from dairy herds and enter the marketing system which involves transportation to public auction markets and then to an abattoir. The objective of this study was to follow cull cows from farm to abattoir and to monitor changes in the cows' condition. From May 2017 to March 2018, data were collected from 20 dairy farms and 3 abattoirs in British Columbia, 1 abattoir in Alberta, and 2 abattoirs in USA. The dairy farms were visited regularly before cows were removed from the herds and a researcher scored the animals for body condition (BCS; 5-point scale), lameness (5-point scale) and udder condition (3-point scale). Trained assessors at the abattoirs also assessed cows' condition at arrival. Mixed effects and glimmix models were used to test the effect of transport on the animals' condition, with cow and farm of origin assigned as random effects. During the study, 1, 220 cull cows were removed from participating farms and 469 of those cows were assessed at one of the participating abattoirs. After leaving the farms, cows spent 79.6 ± 1.9 hours in the marketing system until being processed. Including delays at auctions or assembly yards, about 43% of cows were in transit for 4–6 days and 4% for 7–9 days. Regarding distance, around 16% of cull cows were transported 1, 100 km from farm to abattoir. Cull cows reduced their BCS from 3.1 ± 0.02 at the farm of origin to 2.6 ± 0.03 at the abattoir ( P <0.0001). Lameness did not change, but transport increased the development of acute milk accumulation and udder inflammation from 8% at farm of origin to 41% at the abattoir ( P <0.0001). This information about delays to slaughter and changes in cow condition could help producers make better culling decisions.